Tonga saves its coconuts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The 'tree of life' as it is known in Tonga, the versatile coconut tree, is suffering from competition from other products and from felling. Its gradual disappearance has alerted the Tonga Ministry of Agriculture to the situation, and it is now...